IDENTIFICATION MANUSCRIPT AND CONTENT OF COMMUNITY KNOWLEDGE IN THE EAST COAST OF JAVA 18-21ST CENTURIES - Khair, Najibul; Hanafi, Ahmad; Jodi, Jergian; Ifan Maulana; Jamaludin, Fitah (Institut Pendidikan Indonesia, 2024)
Ancient manuscripts are considered to be the most important and authentic source of the intellectual output of our ancestors. It can also be said that manuscripts are a gift from the predecessors, with which later generations can connect the history of the past with the present. This article discusses the identification of ancient manuscripts and the knowledge content of local communities by focusing on the preservation and conservation patterns of ancient manuscripts. The eastern tip of Java was deliberately chosen as the locus of research and more specifically the Banyuwangi to Jember area, because in this region there are many kinds of manuscripts that are still 'alive' in the community. This research uses descriptive analysis method, the data source or object of this research is all manuscripts found. The data collection techniques used are interviews and literature studies. This research also uses a philological research flow consisting of manuscript inventory and manuscript description, and shows that from the findings of 40 manuscripts made from daluang, 241 made from European paper and 69 made from paper made by the Letjes factory, it can be identified the contents and titles or text identification, it can be seen that these manuscripts contain knowledge of Islamic teachings, for example some manuscripts contain songs that tell about the history of the prophet Muhammad SAW, the prophet Yusuf As, and Javanese shiiran patterns. Keywords: Ancient manuscripts, preservation and conservation, local community knowledge